Corrosion Of Nanocomposite Sn/Ag Coating On Copper Substrate - Azmi, Nurul Atiqah (Universiti Sains Malaysia, 2022)
Sn coating is commonly used as corrosion protection for copper. To improve electrical conductivity, Argentum or Ag can be added into the coating to form composite coating Sn/Ag. However, the addition of nanoparticles must not lead to negative effect to the coating’s properties such as the corrosion resistance. This study is carried out to evaluate effect of adding nanoparticles Ag to the corrosion behavior of Sn coating on copper (Cu) substrate. During electrodeposition process, the operating parameters includes current density 2A and voltage of 1.5 V, stirring speed (400 rpm), 4 minutes electrodeposition process and temperature of 24℃. The effect to corrosion rate of copper substrate coated with Sn and Sn/Ag 10 nm and 100nm nanocomposite coating were studied via immersion and polarization potentiodinamic corrosion tests. The best corrosion properties were obtained with Sn coating compared to Sn/Ag coating. The higher corrosion rate of Sn/Ag coated samples was confirmed by immersion test for 7, 14 and 21 days and potentiodynamic polarization technique was caried out with 1M NaCl electrolyte. The thickness of the coating was also characterized by using SEM. The weight loss and corrosion rate were calculated from these experiments. The Tafel extrapolation method used copper sample as working electrode, platinum electrode as counter electrode and standard calomel electrode as reference electrode. Based on immersion results, increasing duration of Sn and Sn/Ag coated exposure to the corrosive solution causes higher corrosion rate. The corrosion rate of Sn/Ag 10 nm is higher than Sn and Sn/Ag 100. Based on Tafel plot, corrosion rate of copper coated with Sn/Ag 10nm is higher than Sn/Ag coating and Sn coating. Sn coated sample has lowest corrosion rate compared to other Sn/Ag samples which is 0.10262 mm/year and has a higher Ecorr value, -0.80923V compared to Cu-Sn/Ag10 nm and 100 nm samples, -1.0305V and -0.96093V respectively. This indicates that Sn/Ag samples are more reactive and corroded more easily than Sn coated sample.